Coronary revascularization in a patient with cirrhosis and renal failure. Coronary artery bypass grafting in a patient with hepatic cirrhosis and end stage renal disease - Wali Murugesh (Interdisciplinary Academy of Pain Medicine, 2021)
Surgery in a patient with hepatic cirrhosis entails risk of complications and of death. Association of end stage renal disease (ESRD) along with cirrhosis further increases perioperative risk of morbidity and mortality. There are no reports in the literature of patients with liver cirrhosis and ESRD having undergone cardiac surgery. We present a report of a successfully operated case of ESRD with compensated hepatic cirrhosis posted for coronary artery bypass grafting.